2017
DOI: 10.21149/8203
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to promote physical activity for youth with intellectual disabilities

Abstract: Objective. To describe interventions designed to promote physical activity for youth with intellectual disabilities. Materials and methods. A systematic review of nine databases until January 31, 2015 identified 213 citations. The inclusion criteria were: a) the study sample consisted of youth with intellectual disabilities, b) the study implemented an intervention to initiate, increase, or maintain physical activity, and c) quantitative or qualitative data were used to report the effectiveness of the interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 38 publications
5
25
0
1
Order By: Relevance
“…Furthermore, very few evaluations utilised an RCT design. This is consistent with previous literature reporting few RCTs of PA interventions for people with disabilities [55,113]. Many also consisted of modest sample sizes.…”
Section: Risk Of Biassupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, very few evaluations utilised an RCT design. This is consistent with previous literature reporting few RCTs of PA interventions for people with disabilities [55,113]. Many also consisted of modest sample sizes.…”
Section: Risk Of Biassupporting
confidence: 91%
“…Given this success, it is possible that class time PA programs may have a positive impact on the development of children with disabilities attending specialist schools [35]. However, while there are published reviews of general interventions to increase PA participation for children with disabilities [54][55][56] and mainstream classroom-based PA interventions [50,51], to the author's knowledge, no review of class time PA programs implemented in specialist primary schools currently exists. It is therefore unclear whether children who attend specialist schools have opportunities to participate in class time PA programs like their typically developing counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, caregivers and parents often attribute the low levels of physical fitness, activity and motor skills to the cognitive and physical disabilities of the child or adolescent, and thereby underestimate the potential these youngsters have. Previous research has shown that improving the physical fitness, activity, and motor skills in children and adolescents with ID is possible [21][22][23][24][25]. In the authors' experience, current care and support focus mainly on activities of daily living skills, like getting dressed and eating independently, while there is hardly any focus on improving physical fitness.…”
Section: Introductionmentioning
confidence: 90%
“…A Finnish study compared accelerometer‐measured physical activity levels of youth with and without intellectual disability and reported those with intellectual disability were 40% less active than their peers, and none of the children with intellectual disability met the recommended guidelines for physical activity (Einarsson et al., ). Indeed, while it is well‐documented that youth with intellectual disability are less active than peers without disabilities, a recent systematic review concluded there are few published efforts to improve physical activity in this population (Frey, Temple, & Stanish, ). Moreover, the authors reported that none of the studies in this review used direct observation and the best measurement approaches combine multiple measures (objective and observation) to assess intervention impact (Frey et al., ).…”
Section: Introductionmentioning
confidence: 99%